PERBANDINGAN KARAKTERISTIK PADA CAMPURAN BETON DENGAN PENAMBAHAN VARIASI UKURAN LIMBAH STYROFOAM (Universitas Muhammadiyah Palembang, 2022)
Mixing concrete with styrofoam waste could help reduce waste in Indonesia. Aside from reducing theexisting waste, this study also aims to determine the characteristics of concrete against Styrofoam wastesubstitution and the optimum value obtained from the results of its concrete testing. The methodologyused is an experiment that is a research method to determine specific effects. This study uses two sizevariations of Styrofoam waste, small size (2 – 4.75mm) and large (4.75mm – 20mm), using the additionalpercentage of 0%, 15%, 25%, and 35%. As for the testing objects, we are using 42 testing objects with atest age of 7 days and 28 days. From the results of 28 days age test, normal concrete has a split tensilestrength value of 1.91 Mpa concrete with the addition of small size styrofoam waste has rougher surfaceproperties than ordinary concrete and has a split tensile strength value with a percentage of 15%, 25%,35% of 2.07 MPa, 1.54 MPa and 1.70 MPa and the optimum value was obtained at the percentage of15% at 2.07 MPa. Concrete with the addition of large size variations has concrete properties thatproduce voids in the concrete that are larger and result in a lighter weight than normal concrete. Thesplit tensile strength values of concrete with percentages of 15%, 25% and 35% are 1.86 MPa, 1.80 MPa,and 1.43 MPa. The optimum value obtained on this large-size styrofoam occurred at a percentage of 15%at 1.86 MPa.